Perempuan dalam Novel Cantik Itu Luka Karya Eka Kurniawan (Tinjauan Hermeneutika Schleiermacher) - Dinda Febri Yanti Siregar; Mardhiah Abbas (UIN Sumatera Utara, 2023)
Woman’s problems are still an interesting phenomenon to study. How is the discrimination in the distribution of roles and positions between men who are seen as more valuable than women. This study aims to present information about women in the novel Cantik Itu Luka by Eka Kurniawan using the Schleiermacher hermeneutic approach. This study uses a qualitative research method with a review of Schleiermacher’s hermeneutic, namely by analyzing grammatical and psychological interpretatons. The data used in this study is a type of library (library research) by reading and researching topics that are relevant to this research. The finding from this study are that women are interpreted as human beings from a biological and physical perspective, women cannot choose their own lives.the role of women in the domestic sphere is to take care of their children properly and with courtesy. Even in earning a living, women would only works as concubines and prostituses. Not infrequenly when a married women, apart from taking care of her children, there are several women who have to participate in earning a living to stabilize the economy. Women in the novel will always be second class humans where they will receive inappropriate treatment, such as sex harassment and rape.